Some Metal Oxide-Natural Rubber Composites for Gamma- and Low-Energy X-Ray Radiation Shielding - A. Fisli; E. Yulianti; B. Hanurajie; S. G. Sukaryo; M Mashadi; A. K. Rivai; H. Prastanto; M. I. Fathurrahman (Atom Indonesia, 2023)
This work studied protective material consisting of several metal oxide composites (Pb3O4, WO3, SnO2, and Bi2O3)-natural rubber (NR) for X-ray and gamma-ray shielding. The composites were prepared through open milling and vulcanization processes and further characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), rheometry analysis, and density gauge. The attenuation coefficient of the sample was investigated using X-ray generators with voltages ranging from 50 to 140 kV and gamma-ray energies ranging and 356 to 1250 keV, respectively. The experimental results show that the linear attenuation coefficient of NR filled with metal oxides was significantly improved compared to pure NR. For gamma-ray 661 keV, the HVL of NR decreased from 9.0 cm to between 4.4 - 6.2 cm after it was filled with metal oxides. The Bi2O3-NR is the best suitable material for gamma-ray attenuation, followed by Pb3O4-NR, WO3-NR, and SnO2-NR. Meanwhile, for x-rays, the HVL of NR decreased from 2.0 cm to between 0.17 -0.31 cm after it was filled with metal oxides. The proposed metal oxide-NR composites can be appropriate as a flexible protective material for manufacturing wearable radiation shielding products such as gloves, aprons, rubber underwear, and other wearable materials.